Effects of dietary resveratrol supplementation on egg production and antioxidant status - Şahin, Kazım; Akdemir, F.; Orhan, C.; Tuzcu, M.; Hayirli, A.; Şahin, Nurhan. (Elsevier, 2010)
Resveratrol, a polyphenol derived from red grapes, berries, and peanuts, exerts antiinflammatory, antioxidant, and immunomodulatory effects. The objective of this study was to investigate the effects of dietary resveratrol supplementation on performance and serum and egg yolk antioxidant status in quail (Coturnix coturnix japonica). A total of 150 five-week-old quails were allocated randomly to 1 of 3 dietary treatments: basal diet and basal diet supplemented with 200 or 400 mg of resveratrol/kg of diet. Each diet was offered to 10 cages of 5 birds in each from 4 to 16 wk of age. Serum and egg samples were collected at the beginning and end the experimental period to be evaluated for malondialdehyde (MDA), vitamin A, and vitamin E. Data were subjected to analysis of covariance using the MIXED procedure. There was no treatment effect on feed intake, egg production, or egg quality parameters related to shell, yolk, and albumen. There were no effects of resveratrol supplementation on serum and egg yolk vitamin A concentrations. The quails supplemented with resveratrol had a lower serum MDA concentration (0.56 vs. 0.88 mg/L, P < 0.03) and a higher serum vitamin E concentration (5.72 vs. 3.56 mg/L, P < 0.008) than those not supplemented with resveratrol. Moreover, there was a linear decrease in serum MDA concentration (P < 0.02) and a linear increase in serum vitamin E concentration (P < 0.01) as supplemental resveratrol level increased. The treatment groups had less egg yolk MDA concentration than the control group (0.21 vs. 0.15 mu g/g, P < 0.002). Egg yolk MDA concentration decreased linearly in response to increasing dietary resveratrol level (P < 0.0003). In conclusion, inclusion of resveratrol up to 400 mg/kg into quail diets enhanced antioxidant status of birds and eggs. Further studies should investigate the carryover effects of dietary resveratrol supplementation on product quality with respect to shelf life, antioxidant stability, and its nutritive value for human consumption.
Keywords: resveratrol; egg yolk; malondialdehyde; antioxidant status; Japanese quail